Occurrence of micropollutants in the Yesilirmak River Basin, Turkey - Kucuk, Elif; Pilevneli, Tolga; Erguven, Gokhan Onder; Aslan, Sibel; Olgun, Elmas O.; Canli, Oltan; Yetis, Ulku (Springer Heidelberg, 2021)
The European Water Framework Directive (WFD) (2000/60/EC) is the most visionary piece of European environmental legislation that aims to achieve good water status of both surface water and groundwater bodies. The Directive provides a fundamental basis for surface water monitoring activities in the European Member States. The objective of this study is to investigate the occurrence of micropollutants in the Yesilirmak River and to develop a cost-effective monitoring strategy based on spatiotemporal data. A 2-year seasonal monitoring program was conducted between 2016 and 2018, and the water samples were analyzed for 45 priority substances as defined by the WFD and 250 national river basin-specific pollutants. In the basin, 166 pollutants were quantified in at least one of the samples with individual concentrations ranging from 6 x 10(-6)mu g/L to 100 mg/L. Fifty-four pollutants with a frequency of occurrence greater than 5% were selected for further evaluation. Based on statistical evaluation of the data, 20 pollutants were identified as the pollutants of primary concern. These 20 pollutants were grouped under three categories (metals, biocides, and industrial organic compounds) and their spatiotemporal distributions in the basin were assessed to establish a monitoring strategy specific to each pollutant category. The results of the study revealed that the common season for the monitoring of all pollutant categories was the spring. This study provides a generic methodology for the development of a cost-effective water quality monitoring strategy, which can be applicable for use in different basins and pollutant datasets.
Keywords: Priority substances; Spatiotemporal variation; Micropollutants; Water quality; Environmental monitoring; Monitoring strategy; Environmental quality standards